2022
DOI: 10.1155/2022/3425873
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Mathematical Modeling in Cost Control of Medical Equipment Procurement in Public Hospitals

Abstract: The purpose of this study is to strengthen the procurement management of public hospitals and ensure the quality of medical equipment. In this paper, combined with the procurement process of medical equipment in public hospitals, on the basis of RFID technology, a JRP model of random demand for medical equipment procurement in public hospitals is established. At the same time, according to the type and quantity of decision variables, the DE solution algorithm is redesigned, and based on the support of the algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Provide an objective basis for device configuration to support configuration decisions. [15][16] This paper proposes a new medical equipment management mode. Compared with traditional medical equipment management, this mode not only realizes the information of archives simply with the help of the IoT and digital twin technology.…”
Section: Discussionmentioning
confidence: 99%
“…Provide an objective basis for device configuration to support configuration decisions. [15][16] This paper proposes a new medical equipment management mode. Compared with traditional medical equipment management, this mode not only realizes the information of archives simply with the help of the IoT and digital twin technology.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%